2003
DOI: 10.1046/j.1399-0039.2003.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of the effects of Glu/Lys β69 human leukocyte antigen‐DP polymorphism on peptide‐binding specificity

Abstract: The polymorphism at position beta69 of the human leukocyte antigen (HLA)-DP molecule has been associated with susceptibility to several immune disorders and alloreactivity. Using molecular modeling, we have predicted a detailed structure of the HLA-DP2 molecule (carrying Glubeta69) complexed with class II associated invariant chain derived peptide (CLIP) and compared it with the form carrying Lys at beta69 (HLA-DP2K69). Major changes between the two models were observed in the shape and charge distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
37
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 58 publications
(106 reference statements)
5
37
0
Order By: Relevance
“…Pocket 4 of DP2 is deeper, more negatively charged than DP4 , giving it a greater affinity for positively charged nonpolar aromatic residues, such as glutamine (Q), arginine (R), and lysine (K). Furthermore, glycine (G) makes pocket 1 (b84) and pocket 6 (b11) deep and hydrophilic, preferentially-binding hydrophobic and aromatic amino acids, notably phenylalanine (F), and tyrosine (Y) (Berretta et al, 2003;Diaz et al, 2003Diaz et al, , 2005. This predicts that infectious peptides with an 1 FXXKXFXXA/V 9 motif (where X is unknown, and P9 can be A or V) are likely to bind to DP2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pocket 4 of DP2 is deeper, more negatively charged than DP4 , giving it a greater affinity for positively charged nonpolar aromatic residues, such as glutamine (Q), arginine (R), and lysine (K). Furthermore, glycine (G) makes pocket 1 (b84) and pocket 6 (b11) deep and hydrophilic, preferentially-binding hydrophobic and aromatic amino acids, notably phenylalanine (F), and tyrosine (Y) (Berretta et al, 2003;Diaz et al, 2003Diaz et al, , 2005. This predicts that infectious peptides with an 1 FXXKXFXXA/V 9 motif (where X is unknown, and P9 can be A or V) are likely to bind to DP2.…”
Section: Discussionmentioning
confidence: 99%
“…Using a similar approach, Castelli et al (2002) defined three DP supertype clusters with shared amino acid residues in the P1 (b84) and P6 (b11) PBP. However, the P4 peptide-binding pocket, at position b69, also makes an important contribution to antibody and peptide-binding (Arroyo et al, 1995;Chicz et al, 1997), T-cell responses (Berretta et al, 2003;Diaz et al, 2003) and disease susceptibility (Potolicchio et al, 1999;Wang et al, 1999). For this reason we clustered 430 DPB1 alleles into six supertypes based on polymorphisms in three PBP, at positions 11, 69, and 84 of the b1 domain (i.e., pockets 6, 4, and 1).…”
mentioning
confidence: 99%
“…In addition, how does the beryllium moiety interact with this amino acid? To date, no crystal structure for HLA-DP2 or DR13 exists, but HLA-DP2 modeling based on the known crystal structure of HLA-DR1 suggests that the Glu 69 is located on the ␣-helix of the ␤-chain with side groups pointing into the peptide-binding cleft (19,27). Based on HLA-DP2 modeling studies, the Glu 69 appears to be involved in the formation of the P4 pocket (27).…”
Section: Discussionmentioning
confidence: 99%
“…To date, no crystal structure for HLA-DP2 or DR13 exists, but HLA-DP2 modeling based on the known crystal structure of HLA-DR1 suggests that the Glu 69 is located on the ␣-helix of the ␤-chain with side groups pointing into the peptide-binding cleft (19,27). Based on HLA-DP2 modeling studies, the Glu 69 appears to be involved in the formation of the P4 pocket (27). Berretta et al (27) suggested that the altering of the HLA-DP2 molecule with a lysine at position 69 (Lys 69 ) as opposed to a glutamic acid induced significant changes in both the shape and charge distribution of the P4 pocket, as well as the neighboring P6 pocket.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of both types of interaction using the linear interaction energy method 36 did not improve the binding prediction (data not shown). Berretta et al 37 arrived at a similar conclusion after using the intermolecular Coulombic and van der Waals energies to predict binding in pockets 4 and 6 of HLA-DP2. They found the most significant contribution to the total energy came from the van der Waals interactions.…”
Section: Discussionmentioning
confidence: 77%